THE ROLE OF THE UZBEK NATIONAL PRESS IN BRINGING UP THE SOLDIERS IN THE SPIRIT OF PATRIOTISM (Scientific journal of the Fergana State University, 2023)
This article reveals the facts about the formation of front newspapers in the Uzbek national press during World War II, the publication of articles aimed at educating soldiers in the spirit of patriotism, and the heroism of Uzbek soldiers on the battlefield.